The Effect ofConcentration ofSurfactant in Enhanced Oil Recovery (EOR): Viscosity and pH - Mustakim, Rusilah (Universiti Teknologi Petronas, 2005)
Enhanced Oil Recovery or EOR is an advanced recovery methods used to recover more oil at the greater extent. Presently, the challenge in most oil companies is to find new methods and techniques to increase oil recovery or OIIP in their present producing oil fields so that it would cater the ever increasing demand ofthe natural resources. Applications of engineering and technology are crucial in order to make the attempts possible, and the development of Enhanced Oil Recovery (EOR) techniques is one of study of interest to increase the current oil production efficiency. Chemical EOR is a derivative ofthe EOR methods and this technique is considered successful as it applies the usage of surfactants in lowering the interfacial tension of the oil and the rock, thus boosts oil production capability. Thus, it is crucial for these surfactants to be studied and evaluated especially on its physical-chemical properties so that they can be fully utilized and ultimately, able to increase oil recovery rate. In this study, experimental works was carried out at Universiti Teknologi Petronas laboratory. The concentration of the surfactant is varied and the effect to the phase behavior, viscosity and pH was observed. For the determination ofphase behavior, the method is carried out by simulating the surfactant samples in reservoir temperatures in a specialized oven and it is left by a specified time. The classification results are done by physical observation of the samples. As for viscosity determination, viscometer is used to obtain the results. For pH determination, pH indicator was used. For Phase Behavior identification, most of the samples yield type II-, a fair desirable results, and a few of samples managed to obtain type III. The viscosity and pH ofthe solution is increased as the concentration ofthe surfactant increase. In overall, the experimental works yield desirable phase behavior results and verified the increment of viscosity and pH.